Indonesian spatial intelligence for geography teachers - Lili Somantri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Geography subjects study objects and spatial phenomena on the earth's surface; Therefore, in practice, they must understand the application of abstract concepts that include spatial perception. This research uses qualitative research methods in measuring the spatial intelligence of geography teachers. Measurements based on four indicators reflecting spatial intelligence are 1) Blind Map; 2) Natural Resources; 3) Icons or landmarks; and 4) Human resources. Based on the study results, it can be concluded that the spatial intelligence of geography teachers mostly has good spatial intelligence. This is indicated by the results of the analysis in 4 categories, namely 1) the results of the analysis show that the ability of geography teachers in blind map knowledge regarding regional locations in Indonesia is fairly good; 2) the ability of geography teachers in natural resource knowledge regarding the distribution of natural resource locations in Indonesia is quite good; 3) the ability of the geography teacher in knowledge of icons or landmarks regarding the icons or landmarks of districts/cities in Indonesia is fairly good; and 4) the ability of geography teachers in human resource knowledge regarding the distribution of ethnicities and cultures in Indonesia is fairly good.